PENGARUH MATA KULIAH METODOLOGI PEMBELAJARAN DAN MICRO TEACHING TERHADAP PRAKTEK PENGALAMAN LAPANGAN (PPL) DI STAIN CURUP - Siti Afifah (IAIN Bengkulu, 2018)
The purpose of this research is to know a significant influence of methodology learning subject variables toward PPL, a significant influence of micro teaching variables toward PPL, and a significant influence of methodology learning sub- ject and micro teaching variables toward PPL students of Prodi PAI TA. 2016/2017 in STAIN Curup. The quantitative research method with the type of research expost facto was used in this research. The population was all students of Prodi PAI TA.2016/2017 in STAIN Curup which consists of 177 people with a sample of 60 people, and the instruments were documenta- tion and questionnaire. The result showed that there was a significant influence between methodology learning subject towards PPL students with the coefficient of determination (R square) as 0,935, it explained that the influence of methodology learning subject towards PPL students was 93,5 %. Next, there was a significant influence between micro teaching towards PPL students with the coefficient of determination (R square) as 0,572, it explained that the influence of micro teaching towards PPL students was 57,2 %. And there is a significant influence between methodology learning subject and micro teaching toward PPL students of Prodi PAI TA. 2016/2017 in STAIN Curup with the coefficient of determination (R square) as 0,935, it explained that meth- odology learning subject and micro teaching were influenced each other toward PPL students of Prodi PAI TA. 2016/2017 in STAIN Curup as 93,5 %, while the remaining 6,5 % was influenced by other variables besides methodology learning subject and micro teaching.